Host KIR/HLA-C Genotypes Determine HIV-Mediated Changes of the NK Cell Repertoire and Are Associated With Vpu Sequence Variations Impacting Downmodulation of HLA-C - Vollmers, Sarah; Lobermeyer, Annabelle; Niehrs, Annika; Fittje, Pia; Indenbirken, Daniela; Nakel, Jacqueline; Virdi, Sanamjeet; Brias, Sebastien; Trenkner, Timo; Sauer, Gabriel; Peine, Sven; Behrens, Georg M.N.; et al. (Frontiers in Immunology, 2022)
NK cells play a pivotal role in viral immunity, utilizing a large array of activating and inhibitory receptors to identify and eliminate virus-infected cells. Killer-cell immunoglobulin-like receptors (KIRs) represent a highly polymorphic receptor family, regulating NK cell activity and determining the ability to recognize target cells. Human leukocyte antigen (HLA) class I molecules serve as the primary ligand for KIRs. Herein, HLA-C stands out as being the dominant ligand for the majority of KIRs. Accumulating evidence indicated that interactions between HLA-C and its inhibitory KIR2DL types (KIR2DL1/L2/L3) can drive HIV-1-mediated immune evasion and thus may contribute to the intrinsic control of HIV-1 infection. Of particular interest in this context is the recent observation that HIV-1 is able to adapt to host HLA-C genotypes through Vpu-mediated downmodulation of HLA-C. However, our understanding of the complex interplay between KIR/HLA immunogenetics, NK cell-mediated immune pressure and HIV-1 immune escape is still limited. Therefore, we investigated the impact of specific KIR/HLA-C combinations on the NK cell receptor repertoire and HIV-1 Vpu protein sequence variations of 122 viremic, untreated HIV-1+ individuals. Compared to 60 HIV-1- controls, HIV-1 infection was associated with significant changes within the NK cell receptor repertoire, including reduced percentages of NK cells expressing NKG2A, CD8, and KIR2DS4. In contrast, the NKG2C+ and KIR3DL2+ NK cell sub-populations from HIV-1+ individuals was enlarged compared to HIV-1- controls. Stratification along KIR/HLA-C genotypes revealed a genotype-dependent expansion of KIR2DL1+ NK cells that was ultimately associated with increased binding affinities between KIR2DL1 and HLA-C allotypes. Lastly, our data hinted to a preferential selection of Vpu sequence variants that are associated with HLA-C downmodulation in individuals with high HLA-C expression levels and high KIR2DL/HLA-C binding affinities. Altogether, our study provides evidence that HIV-1-associated changes in the KIR repertoire of NK cells are to some extent predetermined by host KIR2DL/HLA-C genotypes. Furthermore, analysis of Vpu sequence polymorphisms indicated that differential KIR2DL/HLA-C binding affinities may serve as an additional mechanism how host genetics impact immune evasion by HIV-1.